Cultural Transformation and Hibridity in The Evolution of Balinese Kebaya Design - Suprapti, Desak Ketut Devi; Sukmadewi, Ida Ayu Kade Sari (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This study examines the evolution of Balinese kebaya design as a representation of cultural transformation and hybridity amidst modernization and globalization. Kebaya, a traditional blouse for Indonesian women, has shifted from everyday wear to formal wear. The development of technology and communication has driven significant changes in kebaya design, giving rise to contemporary kebaya that is more adaptive to an active and attractive modern lifestyle. However, modernization brings challenges in maintaining the traditional values of kebaya, raising concerns about the loss of cultural identity. The purpose of this study is to analyze the evolution of Balinese kebaya design based on the theory of cultural transformation and hybridity in an effort to preserve cultural heritage. The method used is descriptive qualitative, with data collection through literature studies, observations, and interviews. The results of the study indicate that the evolution of Balinese kebaya is a clear manifestation of cultural transformation. Cultural transformation can be seen from the shift in the function of kebaya from everyday wear to diverse fashion clothing, with modifications in shape, material, and style that are not bound by traditional rules, reflecting the shift in community values. Hybridity is reflected in the combination of new materials such as velvet, silk, and lace from global influences, as well as the combination of traditional techniques with modern technology. Contemporary kebaya, with its collar and sleeve variations, and the use of modern materials, shows local and global elements interacting, creating a new, dynamic, and relevant cultural expression. This hybridity is seen as an adaptive strategy to maintain the relevance of cultural heritage in the modern era, without losing its cultural roots. Further research is recommended to explore the economic impact of contemporary kebaya on local craftsmen and the fashion industry in Bali, as well as analyzing the perception of the younger generation towards the use of traditional versus contemporary kebaya.